2015
DOI: 10.4238/2015.august.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression analysis of the prophenoloxidase activating factor from the mud crab Scylla paramamosain

Abstract: ABSTRACT. Prophenoloxidase activating factors (PPAFs) are a group of clip domain serine proteinases that can convert prophenoloxidase (pro-PO) to the active form of phenoloxidase (PO), causing melanization of pathogens. Here, two full-length PPAF cDNAs from Scylla paramamosain (SpPPAF1 and SpPPAF2) were cloned and characterized. The full-length SpPPAF1 cDNA was 1677 bp in length, including a 5'-untranslated region (UTR) of 52 bp, an open reading frame (ORF) of 1131 bp coding for a polypeptide of 376 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…This may be due to copper being a key component of the PO enzyme, with excessive dietary copper producing a toxic impact inducing toxic stress [68]. Moreover, ProPO is also a copper-containing proenzyme and a key component of the phenoloxidase proenzyme system [68]. In the present study, a numerically lower transcript level of proPO was found in mud crab fed the diet with the highest level of dietary copper, albeit not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…This may be due to copper being a key component of the PO enzyme, with excessive dietary copper producing a toxic impact inducing toxic stress [68]. Moreover, ProPO is also a copper-containing proenzyme and a key component of the phenoloxidase proenzyme system [68]. In the present study, a numerically lower transcript level of proPO was found in mud crab fed the diet with the highest level of dietary copper, albeit not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
“…These results are somewhat in agreement with the present study in mud crab where significantly lower activities of hemolymph PO activity were recorded in crabs fed the two highest levels of copper. This may be due to copper being a key component of the PO enzyme, with excessive dietary copper producing a toxic impact inducing toxic stress [68]. Moreover, ProPO is also a copper-containing proenzyme and a key component of the phenoloxidase proenzyme system [68].…”
Section: Discussionmentioning
confidence: 99%
“…As part of the ongoing effort to support and enhance the aquaculture of Scylla species, much work has focused on understanding the biology of these crabs (e.g., Bao et al, 2015;Chen et al, 2015;Girish et al, 2015;Gong et al, 2015;Huang et al, 2014Huang et al, , 2015Ikhwanuddin et al, 2014;Kornthong et al, 2014;Sun et al, 2015;Wang et al, 2015aWang et al, , 2015bXie et al, 2014;Zeng et al, 2016;Zhao et al, 2015). One outcome of these studies has been the development of extensive transcriptomic resources for several Scylla species (e.g., Bao et al, 2015;Kornthong et al, 2014;Ma et al, 2014;Xie et al, 2014), including S. olivacea, for which approximately 160,000 transcriptome shotgun assembly (TSA) sequences are now available in GenBank (e.g., BioProject Accession No.…”
Section: Introductionmentioning
confidence: 99%
“…Since crustaceans have no adaptive immunity memory cells to produce immunoglobulins, they mainly depend on innate immune systems for host defence (35) . The prophenoloxidase (proPO) system is considered as a constituent of the immune system and probably responsible, at least in part, for the non-self recognition process of the defence mechanism in crustaceans, when transformed to the active form (PO) by metal ions (55) , with PO being one of the most important enzymes involved in the innate immune system of invertebrates (56) . In the present study, crabs fed the diet with 44•5 mg/kg Zn had significantly lower PO activity in haemolymph than those fed the 97•3 mg/kg Zn diet, indicating that the appropriate dietary Zn level could activate PO activity and promote immune responses.…”
Section: Discussionmentioning
confidence: 99%